Structural responses on a BMX racing bicycle - Koellner, A.; Cameron, C. J.; Battley, M. A. (Procedia Engineering, 2014)
Acceleration and strain responses of a BMX bicycle in common cycling situations and in a race simulation are investigated. A comprehensive set of data is acquired by a specifically developed measurement and analysis system. The data-acquisition and signal conditioning device is run by customised application software enabling a sampling frequency of 1000 Hz for simultaneous acquisition of 28 measurement channels; 24 channels for strain and 4 channels for acceleration. Comprehensive results of strains and accelerations are presented, with strains being measured on fork, handlebar, top tube, down tube, seat stays and chain stays and accelerations being obtained at both dropouts, the stem and the seat clamp. The data provides quantitative results on strain levels throughout the frame, and in local regions where failure is known to occur. Accelerations from -25 g to 43 g and magnitudes of strain of up to 2750 µe are obtained. An estimate of maximum stress of 190 MPa generated within the frame is calculated. Shear strains which are up to 84% higher than were obtained in static tests are generated in race simulations. The paper provides significant insight into the complexity of the dynamic loads a BMX bicycle - rider system is subjected to, providing the basis for future optimisations of BMX bicycle frames.